2012 IEEE International Instrumentation and Measurement Technology Conference Proceedings 2012
DOI: 10.1109/i2mtc.2012.6229557
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy and indoor environment quality sensing for smart buildings

Abstract: This paper presents a technique to determine the occupancy and indoor environment quality (IEQ) in buildings by enhancing physical measurements from a distributed sensor network with a statistical estimation method. The research is motivated by the increasing demand for improving energy efficiency while maintaining healthy and comfortable environment in buildings. Features representing the occupancy level and the relative changes are extracted from a suite of sensors: passive infra-red (PIR) sensors, Carbon Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 11 publications
0
47
0
1
Order By: Relevance
“…Time series models have been applied to many cases of outdoor environment 74,75 and building energy studies. 35 In indoor environments, time series models have also been applied to forecast temperature, 76 relative humidity, 76,77 CO 2 concentration, [76][77][78] and CO concentration. 78 The four parameters can be measured continuously using low-cost online sensors.…”
Section: Time Series Modelsmentioning
confidence: 99%
“…Time series models have been applied to many cases of outdoor environment 74,75 and building energy studies. 35 In indoor environments, time series models have also been applied to forecast temperature, 76 relative humidity, 76,77 CO 2 concentration, [76][77][78] and CO concentration. 78 The four parameters can be measured continuously using low-cost online sensors.…”
Section: Time Series Modelsmentioning
confidence: 99%
“…Examples of additional algorithms are discussed in [34] and [35]. In [36], an Autoregressive Hidden Markov Model (ARHMM) was developed to model the occupancy pattern using data from PIR sensors, carbon dioxide, concentration and relative humidity sensors. It was found that the algorithm has an average estimation accuracy of 80.78% and outperforms the other previously mentioned methods.…”
Section: Algorithms For Occupancy Detectionmentioning
confidence: 99%
“…In summary, the EM-algorithm iterates between the E-Step to compute the sufficient statistics P(q t = i, q t+1 = j|Y ) and P(q t = i|Y ) with Equations (18), (19), (20), and (21) while fixing the parameters in (17a)−(17d), and the M-Step to update the parameters in (17a)−(17d) while fixing the sufficient statistics until some convergence criterion on the expected value of (15) is reached. .…”
Section: Parameter Estimation and Inferencementioning
confidence: 99%